A novel protocol for a "Citizen Panel" for diverse Public and Participant Involvement in the review and development of the process to access data in the UK Longitudinal Linkage Collaboration Trusted Research Environment - Lidis Garbovan; Betty O. Idemudia; Robin Flaig; Kirsteen Campbell; Katharine Evans; Andy Boyd; Sarah Cunningham-Burley; Emma L. Turner (International Journal of Population Data Science, 2025)
Background Researchers can apply to UK Longitudinal Linkage Collaboration (UK LLC) to access Longitudinal Population Study (LPS) data linked to health, non-health administrative and geo-environmental data. This paper describes the protocol for the "UK LLC Citizen Panel": a new method of incorporating a diverse public in decisions about the acceptability and suitability of the UK LLC data access process. The UK LLC Citizen Panel aims to embed public feedback and perceptions into UK LLC's data access process design and decision-making.